Legal Responsibility for Misuse of Online Crowdfunding - Eko Muljono, Bambang; Khoiri, Ach.; Royani , Achmad; Nuruhul Yajlul, Ahmad (Jurnal Independent, 2025)
The phenomenon of abuse of online donation funds by recipients has become a legal issue that requires serious attention, particularly in the realm of civil law. This research aims to address two main problem formulations. First, what are the legal rules regarding the acceptance and management of online donation funds? Second, what is the legal accountability for recipients of donations who commit abuse? This research employs a normative juridical method with a regulatory approach (statute approach). Primary legal materials include: Law No. 9 of 1961 concerning the Collection of Money or Goods, the Civil Code Article 1365, Government Regulation No. 29 of 1980 concerning the Implementation of Collection of Donations, and Minister of Social Affairs Regulation No. 8 of 2021 concerning the Organization of Fundraising. From the discussion results, the researcher concludes that first, the collection of money or goods, which can be interpreted as crowdfunding according to Article 1 of Law No. 9 of 1961, means any effort to obtain money or goods for development in the fields of social welfare, mental/religious/spiritual, physical, and cultural must have prior permission in accordance with applicable legal regulations and the elements contained therein. Second, based on Article 1365 of the Civil Code, any unlawful act that causes loss to another person results in the obligation of the perpetrator to compensate for such loss. In this case, a recipient of donations who uses the funds not according to their intended purpose may be held civilly accountable if it is proven to meet the elements of unlawful acts, namely the existence of an unlawful act, fault, loss, and a causal relationship between the act and the loss. Clarification of these elements serves as the basis for determining civil legal responsibility. This research underscores the importance of tighter legal regulation and oversight of digital donation activities to provide legal protection for donors.